The Basic Courses for the Study of Religions at the University of Southern Denmark. (July 2015) - Jensen, Tim
Abstract This essay is part of a collection of short essays solicited from authors around the globe who teach religion courses at the college level (not for professional religious training). They are published together with an introduction in Teaching Theology and Religion 18:3 (July 2015). The authors were asked to provide a brief overview of the curriculum, student learning goals, and pedagogical techniques employed in their courses.